The critical role of threat detection and movement behavior assessment: Identifying key concepts, research scope, and gaps—a scoping review - Adiarte, Sandra; Carbon, Claus-Christian; Orr, Robin; Canetti, Elisa F. D. (Frontiers in Psychology, 2025)
Police officers face the challenging task of identifying potential threats daily. Failure to identify these threats soon enough can lead to physical injury, and, in the case of an armed offender, a fatal outcome. As such, the ability of an officer to identify an armed threat is critical. This scoping review aimed to identify and synthesize current literature regarding the ability of police officers or CCTV operators to identify an immediate source of threat. A systematic and repeated search of academic databases (Ovid Medline, PubMed, SportDiscus, Web of Science, and Embase) was finalized 26th of November 2024. All articles were screened for relevance against inclusion and exclusion criteria. A snowballing approach was employed, and the reference lists of pertinent studies were searched for additional sources of information. From an initial 14,812 records, four studies specifically met the eligibility criteria. All these studies evaluated the ability of law enforcement officers to identify threats and assessed the performance of the officers by investigating risk estimates and detection tests. Various video data-based tasks and tests have been used to assess the ability to identify upcoming or acute threats. Limited research has been published of studies investigating police officer concealed threat detection approaches, methods, and outcomes, highlighting a paucity of research in this critical field.